Post-operative sepsis-induced acute respiratory distress syndrome: risk factors for a life-threatening complication - Miguel Bardají-Carrillo; Miguel Bardají-Carrillo; Miguel Bardají-Carrillo; Marta Martín-Fernández; Marta Martín-Fernández; Marta Martín-Fernández; Rocío López-Herrero; Rocío López-Herrero; Rocío López-Herrero; Rocío López-Herrero; Juan Manuel Priede-Vimbela; Juan Manuel Priede-Vimbela; et al. (Frontiers in Medicine, 2024)
IntroductionPrevalence and mortality of the acute respiratory distress syndrome (ARDS) in intensive care units (ICU) are unacceptably high. There is scarce literature on post-operative sepsis-induced ARDS despite that sepsis and major surgery are conditions associated with ARDS. We aimed to examine the impact of post-operative sepsis-induced ARDS on 60-day mortality.MethodsWe performed a secondary analysis of a prospective observational study in 454 patients who underwent major surgery admitted into a single ICU. Patients were stratified in two groups depending on whether they met criteria for ARDS. Primary outcome was 60-day mortality of post-operative sepsis-induced ARDS. Secondary outcome measures were potential risk factors for post-operative sepsis-induced ARDS, and for 60-day mortality.ResultsHigher SOFA score (OR 1.1, 95% CI 1.0–1.3, p = 0.020) and higher lactate (OR 1.9, 95% CI 1.2–2.7, p = 0.004) at study inclusion were independently associated with ARDS. ARDS patients (n = 45) had higher ICU stay [14 (18) vs. 5 (11) days, p < 0.001] and longer need for mechanical ventilation [6 (14) vs. 1 (5) days, p < 0.001] than non-ARDS patients (n = 409). Sixty-day mortality was higher in ARDS patients (OR 2.7, 95% CI 1.1–6.3, p = 0.024). Chronic renal failure (OR 4.0, 95% CI 1.2–13.7, p = 0.026), elevated lactate dehydrogenase (OR 1.7, 95% CI 1.1–2.7, p = 0.015) and higher APACHE II score (OR 2.7, 95% CI 1.3–5.4, p = 0.006) were independently associated with 60-day mortality.ConclusionPost-operative sepsis-induced ARDS is associated with higher 60-day mortality compared to non-ARDS post-operative septic patients. Post-operative septic patients with higher severity of illness have a greater risk of ARDS and worse outcomes. Further investigation is needed in post-operative sepsis-induced ARDS to prevent ARDS.